Economic Development of the Mekong Delta in Vietnam (University of Groninger, 2008)
This book originates from the NPT/VNM project "enhancing the teaching and research capacity to assist small - and medium - sized enterprises and farm households in the Mekong Delta. Content: The importance of private enterprises in the Mekong Delta, examine marketing structure and marketing channels of different products in the Mekong Delta, detailed aspects of farming in the Mekong Delta.